Ophthalmic Complications Associated with Direct Oral Anticoagulant Medications. (3rd September 2017) - Shieh, Wen-Shi; Sridhar, Jayanth; Hong, Bryan K.; Maguire, Joseph I.; Rahimy, Ehsan; Shahlaee, Abtin; Ho, Allen C.; Hsu, Jason; Regillo, Carl D.; Chiang, Allen
ABSTRACT: Objective : To describe the clinical features and management of six patients with ocular complications associated with direct oral anticoagulants (DOACs). Methods : The medical records of all adult patients known to be taking a DOAC and with an unusual bleeding event at a large tertiary referral center over a one-year period were reviewed. Patients with less than one-month follow-up were excluded. Data collection included relevant clinic notes, operative reports, surgical videos, and clinical images (fundus photography, optical coherence tomography, B-scan ultrasonography, and fluorescein angiography). Results : Six eyes in six patients were identified with an unusual bleeding event associated with DOAC use. One patient was taking apixaban, two patients were taking dabigatran, and three patients were taking rivaroxaban. Two patients had large submacular hemorrhage (including one with vitreous hemorrhage breakthrough), three patients had vitreous hemorrhage, and one patient had recurrent hyphema. Presenting visual acuity ranged from 20/40 to light perception. Three individuals required therapeutic and/or diagnostic pars plana vitrectomy for vitreous hemorrhage. Final visual acuity ranged from 20/25 to count finger vision. The associated DOAC was permanently discontinued in two of the six cases. Follow-up was one to four months from onset of identified DOAC-related complication. Conclusions : DOAC use may be associated with ocular bleeding. Ophthalmologists should be aware of potential hemorrhagic complications and obtain consultation with primary providers regarding DOAC cessation guidelines.